The Trade-Off Between Format Familiarity and Word-Segmentation Facilitation in Chinese Reading - Chen, Mingjing; Wang, Yongsheng; Zhao, Bingjie; Li, Xin; Bai, Xuejun (Frontiers in Psychology, 2021)
In alphabetic writing systems (such as English), the spaces between words mark the word boundaries, and the basic unit of reading is distinguished during visual-level processing. The visual-level information of word boundaries facilitates reading. Chinese is an ideographic language whose text contains no intrinsic inter-word spaces as the marker of word boundaries. Previous studies have shown the basic processing unit of Chinese reading is also a word. However, findings remain inconsistent regarding whether inserting spaces between words in Chinese text promotes reading performance. Researchers have proposed there may be a trade-off between format familiarity and the facilitation effect of inter-word spaces. To verify this, this study manipulated the format familiarity via reversing the Chinese reading direction from right to left to investigate this issue. The purpose of Experiment 1 was to examine whether inter-word spaces facilitated Chinese reading in an unfamiliar format. Experiment 1 was conducted with 40 native Chinese undergraduates and four format conditions: unspaced format, inter-character spaced format, inter-word spaced format and non-word spaced format. Eye movements during the reading process were recorded via EyeLink 1000 (SR Research, Canada). The results showed faster reading speed and shorter total reading time for the inter-word spaced format, which indicates the inter-word spaces promoted Chinese reading performance in the unfamiliar format. Based on this finding, Experiment 2 examined whether the facilitation effect of inter-word spaces would change after improving the format familiarity; this experiment was conducted with 40 native Chinese undergraduates who did not participate in Experiment 1. To improve their format familiarity, the participants spent 30 minutes a day over a duration of 10 days reading reverse Chinese text from right to left. After reading training, participants’ eye movements were recorded by EyeLink 1000 (SR Research, Canada) during the reading process. There was no significant difference between the total reading time and reading speed in the inter-word spaced format and unspaced format, which suggests facilitation effect of inter-word spaces in Chinese reading disappeared in Experiment 2. The combined results of the two experiments suggest that there is indeed a trade-off between format familiarity and the facilitation of word segmentation.